Framing Media Online: Analisis Model Pan dan Kosicki Pada Pemberitaan Konser Seventeen Right Here Jakarta di Detik.com dan Kompas.com - Fibriyanti, Fauzziyah; Fajar Wulandari, Yulianti; Hamid, Ali Imron (Comit: Communication, Information and Technology Journal, 2025)
Coverage of Seventeen's "Right Here" concert in Jakarta reported by online media Detik.com and Kompas.com. Through the selection, emphasis, and arrangement of information in news texts, mass media play an important role in shaping public opinion. In this study, a qualitative approach was used, and the framing analysis method of the Pan & Kosicki model (1993) was employed. This model includes four discourse structures: syntax, script, thematic, and rhetorical. Data was collected from eight news articles published from February 4-10, 2025. The results of the analysis showed that Detik.com framed the news in a sensational style, emphasized conflict and public emotions, and used quotes from social media. Meanwhile, Kompas.com framed the issue with a neutral narrative style, emphasizing institutional information structures and official statements.Both media show their own journalistic features through their framing. This study found that framing shapes social meanings and perceptions of popular culture events in addition to conveying facts. These results support mass communication research and show how important media literacy is to understand the construction of reality made by online media.